Analisis Pelaksanaan Pengadaan Barang/Jasa Melalui Elektronik Pada Pemerintahan Kabupaten Banyumas - Pupu Sriwulan Sumaya (AWATARA Publisher, 2024)
E-procurement has benefits for agencies or system developers as well as for all providers of goods/services and the wider community who want to know the implementation process, they can get prices for multiple offers and the process uses simple administration. On the other hand, providers of goods/services can also reduce administrative costs, increase opportunities for companies, encourage healthy competition, and can make business opportunities available to everyone. Apart from that, e-procurement is considered capable of providing easier management, faster buying and selling processes, and reducing transaction costs, good coordination, and also increasing collaboration between providers of goods/services. Information technology can make costs better and the public procurement system more diverse.